Analyses of genetic diversity in Cuban rice varieties using isozyme, RAPD and AFLP markers - Fuentes, J.L; Escobar, F.; Álvarez, A.; Gallego Sánchez, Gerardo J.; Duque E., Myriam Cristina; Ferrer, M; Deus, J.E.; Tohme, Joseph M. (Springer, 1999)
A survey of the genetic diversity among the major cuban rice cultivars was conducted using isozyme, RAPD and AFLP markers. Polymorphisms were detected for esterases, peroxidases, alcohol dehydrogenases and polyphenoloxidases systems; 21 RAPD primers and four AFLP primer combinations. Heterozygosity arithmetic mean value (Hav(p)), the effective multiplex ratio (EMR) and the marker index (MI), were calculated for isozyme, RAPD and AFLP markers. The mean value of genetic similarity among the different varieties was 0.92 for isozyme, 0.73 for RAPD and 0.58 for AFLP analyses. Thus, AFLP were able to detect polymorphisms with higher efficiency than RAPD (+15%) and isozyme (+34%). Data from the isozyme, RAPD and AFLP analyses were used to compute matrices of genetic similarities. The efficiency of the UPGMA for the estimation of genetic relatedness among varieties was supported by cophenetic correlation coefficients. The resulting values indicated that the distortion level for the estimated similarities was minimal. The correlation coefficients obtained by the Mantel matrix correspondence test, which was used to compare the cophenetic matrices for the different markers, showed that estimated values of genetic relationship given for isozyme and RAPD markers (r = 0.89), as well as for AFLP and RAPD markers (r = 0.82) were properly related. However, AFLP and isozyme data showed only moderate correlation (r = 0.63). Although the genetic variability found among the different cultivars was low, both RAPD and AFLP markers proved to be efficient tools in assessing the genetic diversity of rice genotypes.